Significance of Sonographic Characterization and FNAC of Small Size Thyroid Nodules (Medical Forum Monthly, 2024)
Objective: The purpose of this study is to determine the accuracy of various ultrasound characteristics of small size thyroid nodules in the predication of malignancy and the usefulness of ultrasound guided FNAC of these nodules.Study Design: Experimental / analytic study.Place and Duration of Study: This study was carried out at Radiology Department Services Hospital, Lahore from October 2011 to September 2012.Materials and Methods: This study was conducted on 70 patients, in whom 76 thyroid nodules 4mm to 10mm in size were biopsied. Diagnostic ultrasound was performed with high frequency linear probe for the evaluation of following ultrasound characteristics, internal structure, echogenicity, margins, posterior acoustic shadowing, height to width ratio, halo around the nodules, calcifications and vascular flow on Doppler scan. Each character was correlated with the results of FNAC to determine the accuracy of the feature in the prediction of malignancy.Results: Out of 76 FNACs of 4mm to 10mm size thyroid nodules 8(10.5%) biopsies did not yield significant cytological specimen. Another 8(10.5%) specimen were classified as indeterminate so no further analysis was done. The rate of malignancy among nodules on final diagnosis was 20%. The most accurate sonographic features associated with malignancy were posterior acoustic shadowing (88.3%), taller than wider (83%), Halo around the nodule (80%) and calcification (70%). Conclusion: Small size thyroid nodules are associated with significant risk of malignancy. Certain sonographic characteristics can be used to measure the risk of malignancy. FNAC of these nodules can be safely and accurately performed with high diagnostic rate.